Tissue-resident macrophages co-develop with myocardial tissue in human induced pluripotent stem cell-derived organoids - Rockel, Anna Frederike; Brunnbauer, Tobias; Wagner, Nicole; Gerull, Brenda; Ergün, Süleyman; Wörsdörfer, Philipp (Frontiers in Cell and Developmental Biology, 2025)
The heart is the first functional organ to develop during embryogenesis, forming in parallel with the vasculature and hematopoietic cell lineages. To advance our understanding of human cardiac development and disease, human induced pluripotent stem cell (iPSC)-derived cardiomyocytes offer a promising in vitro model. However, conventional 2D cultures lack the complexity required to recapitulate the intricate interactions of different cell types leading to fully functional and mature cardiac tissue. Here, we present a human iPSC-derived 3D organoid model that develops a functional myocardium composed of cardiomyocytes and fibroblasts, capable of spontaneous rhythmic contractions. The organoid is interspersed with a branched network of endothelium-lined cavities, endothelial cords and capillary-like structures. Additionally, hemogenic endothelium co-develops with the cardiac tissue, giving rise to erythrocytes and CCR2- tissue-resident macrophages that integrate into the myocardium. The model represents a complex 3D cell culture platform to study human heart tissue development with all the involved cell types (cardiomyocytes, fibroblasts, endothelial cells, macrophages), paving the way for new insights into the role of macrophages in cardiac development and disease.